2018
DOI: 10.2147/ott.s182786
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect of <em>Drimia maritima</em> bulb extract and induction of mitochondrial apoptotic signaling in human breast cancer cells, MCF-7 and MDA-MB-468

Abstract: BackgroundDrimia maritima (D. maritima) is a plant belonging to the family Asparagaceae, which has been used for the treatment of several ailments including cancer around the world. To our knowledge, there is no comprehensive study about the molecular mechanisms of anticancer activity of this plant, yet.Materials and methodsIn the current study, cell viability, apoptosis induction, ROS production, mitochondrial apoptotic pathway, and ER stress mediators have been evaluated in breast cancer cells, MCF7, and MDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Previously, D. maritima induced cell death in human breast cancer cells via the intrinsic apoptotic pathway [ 119 ]. Baccatin III promoted apoptosis in JR4-Jurkat cells with possible participation of anti-apoptotic Bcl-2 and mitochondrial membrane damage [ 120 ]. Furthermore, limonin glucoside induced apoptosis through a reduction in the transcription ratio of Bcl-2/Bax and initiating the release of cytochrome c from mitochondria to cytosol, which confirm the activation of the intrinsic apoptotic pathway in SW480 colon cancer cells [ 121 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, D. maritima induced cell death in human breast cancer cells via the intrinsic apoptotic pathway [ 119 ]. Baccatin III promoted apoptosis in JR4-Jurkat cells with possible participation of anti-apoptotic Bcl-2 and mitochondrial membrane damage [ 120 ]. Furthermore, limonin glucoside induced apoptosis through a reduction in the transcription ratio of Bcl-2/Bax and initiating the release of cytochrome c from mitochondria to cytosol, which confirm the activation of the intrinsic apoptotic pathway in SW480 colon cancer cells [ 121 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Hamzeloo-Moghadam reported that the IC50 values for the non-hemolytic ethanol extract of U. maritima against breast cancer MCF7 cells were 11.01 µg/mL. Additionally, IC50 values for the non-hemolytic acetone extract of U. maritima against breast cancer MCF7 cells was 6.01 µg/mL, while the Doxorubicin drug (positive control) exhibited a cytotoxic effect with a higher IC50 value (52.35 µg/mL) [ 19 ]. Another example is the study conducted by Obeidat and Sharan, which found that the effective doses of D. maritima that inhibited 50% of growth (IC50) of MCF-7 and MDA-MB-468 cells were 20.48 ± 1.17 µg/mL and 25.74 ± 2.05 µg/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Considering annexin V’s high affinity to PS binding, it was used to identify early apoptotic rate. PI, a red fluorescent intercalating dye, was used as a DNA stain to study dead cells or late apoptotic rate ( Hamzeloo-Moghadam et al ., 2018 ).…”
Section: Methodsmentioning
confidence: 99%